UNIVERSITAS MALIKUSSALEH DELEGATION VISIT STRENGTHENS TIES WITH USM - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 29 September 2015 – The Deputy ViceChancellor (Academic and International Affairs) Universiti Sains Malaysia (USM), Professor Dato' Dr. Ahmad Shukri Mustapa Kamal today received a courtesy visit from the delegates of Universitas Malikussaleh Aceh, Indonesia (UNIMAL), led by its Rector, Professor Dr. Apridar at the USM Chancellory Conference Room.